Integrated Analysis of the CircRNA-Based ceRNA Network in Renal Fibrosis Induced by Ischemia Reperfusion Injury - Wei, Lei; Yu, Zhixiang; Liu, Limin; Zhou, Ying; Bai, Xiao; Wang, Liya; Bai, Ming; Sun, Shiren (Frontiers in Genetics, 2022)
Background: Circular RNAs (circRNA) which have broad post-transcriptional regulatory potencies are involved in the pathogenesis of fibrotic diseases, and hold great promise as diagnostic biomarkers and therapeutic targets. However, their specific roles in renal fibrosis remain elusive. Methods: The robust unilateral renal ischemia reperfusion injury (UIRI) mouse model was established to recapitulate the pathophysiology of renal fibrosis. The expressions of circRNAs, miRNAs and mRNAs were profiled by high-throughput RNA sequencing technology. Results: In total, 4983 circRNAs, 216 miRNAs and 6371 mRNAs were detected to be differentially expressed in UIRI-induced fibrotic kidneys. Candidate circRNAs and miRNAs were validated by RT-qPCR in both UIRI and unilateral ureteral obstruction mouse models. Bioinformatic analysis indicated that the parental genes of the differentially expressed circRNAs were predominantly implicated in focal adhesion, adhesion junctions and regulation of actin cytoskeleton pathways. Through circRNA-miRNA-mRNA construction, we identified two hub genes, circSlc8a1 and circApoe, that targeted a large numbers of differentially expressed miRNAs and mRNAs related to metabolism and cytokine-cytokine receptor pathways, respectively. Conclusion: CircRNAs were dysregulated in UIRI model and might be potentially involved in the pathogenesis of renal fibrosis. Research efforts should focus on unravelling the functions of aberrantly expressed circRNAs in renal fibrosis to uncover biomarkers that would enable early diagnosis and design of prompt therapeutic interventions to prevent disease progression.